Market orientation practices among small and medium hotels (SMHS) in tourist destination island of Langkawi - Abdul Aziz Ab Latif; Ismail Omar; Hamzah Omar (2007)
The purpose of the study is to investigate the underlying components of market orientation practices and their effect on the Small and Medium Hotels (SMHs) performances on tourist destination island of Langkawi. Fifty SMHs were randomly selected from a sampling frame of a list of SMHs registered with Malaysian Tourism Board. For data collection purposes, structured questionnaires were personally delivered and collected. Rotated component matrix factor analysis of the data extracted four underlying factors that explain seventy nine point four six percent of the total variances and alpha reliability coefficient of ninety eight percent. Those components were named as customer orientation, interfunctional orientation, service orientation, and competitor orientation. One sample Kolmogorov‐Smirnov Test indicates that SMHs in Langkawi practices market orientation in their operations and businesses. However, the finding of the study showed that their performances in 1998 was lower than 1997. We believe that this outcome is due to the effect of national and regional economic downturn in 1998.